The Humanistic Note in Iqbal - M. Abdul-Huk (International Institute of Islamic Thought, 2006)
What Is Humanism? Like any other “ism,” humanism is a term of vague and varied usage, perhaps finally identifiable, but one from which certain aspects may be picked out. Humanism, as a term for a certain attitude of mind, has a somewhat curious historical genesis. I say curious, because the attitude itself is much older than the period by which it was given this label – is, perhaps, as old as human nature itself. However, as a term of historical genesis, humanism came to be applied to the view of life that began to oppose and be contradistinguished from the older medieval view of life (since called “divinism”) from the time of the European Renaissance. Here, I can do no better than quote almost in extenso Professor Ramsay Muir’s description of the essential difference between the divinism of the Middle Ages and the humanism of the periods both before and after the “divinistic” interregnum: The best men of the Middle Ages thought of the world as a place of struggle and discipline in preparation for another world; the Greeks thought of it as a place of wonder and beauty which ought to be explored and enjoyed, and they thought little and vaguely about the idea of another world. … for the best minds of the Middle Ages the highest duty of Man was to conquer his passions and to subordinate his arrogant will to the will of God by obeying the rules of life set forth by God’s Church. For the Greeks, Man’s highest duty was to make the most of himself and to develop all his powers of mind and body in the most harmonious way, so that he might enjoy the beauty of the world and be able to seek the truth ...